Hospitalization for adverse events under abiraterone or enzalutamide exposure in real‐world setting: A French population‐based study on prostate cancer patients. Issue 1 (22nd July 2021) - Scailteux, Lucie‐Marie; Despas, Fabien; Balusson, Frédéric; Campillo‐Gimenez, Boris; Mathieu, Romain; Vincendeau, Sébastien; Happe, André; Nowak, Emmanuel; Kerbrat, Sandrine; Oger, Emmanuel
Abstract : Aims: Safety profiles of abiraterone and enzalutamide rely mainly on Phase III clinical trials. Our objective was to estimate the incidence rate ratio (IRR) for certain adverse events leading in real life to hospitalization (atrial fibrillation, acute heart failure, ischaemic heart disease, acute kidney injury [AKI], ischaemic stroke, torsade de pointe/QT interval prolongation, hepatitis and seizure), comparing abiraterone to enzalutamide. We also set out to discuss previously identified safety signals. Method: Using the French National Health Insurance System database, all patients newly exposed to abiraterone or enzalutamide between 2013 and 2017 and followed until 31 December 2018 were targeted. IRRs for each event were estimated using a Poisson model in a sub‐population of patients without contraindications or precautions for use for either treatment. Results: Among 11 534 new users of abiraterone and enzalutamide, AKI (IRR 1.42, 95% CI: 1.01–2.00), liver monitoring suggestive of hepatic damage (IRR 3.06, 95% CI: 2.66–3.53) and atrial fibrillation (IRR 1.12, 95% CI: 1.05–1.19) were significantly more often observed with abiraterone than with enzalutamide. Conclusion: Our study provides knowledge on abiraterone and enzalutamide real‐life safety profiles, especially for events leading to hospitalization. Despite several limitations, including the lack of clinical data, the safety signal for AKI under abiraterone is in line with results of an analysis of the French pharmacovigilance database, which requires further specific investigations. Enlightening the clinicians' therapeutic choices for patients treated for prostate cancer, our study should lead to clinicians being cautious in the use of abiraterone. Abstract :